Lagrangian three-dimensional transport and dispersion by submesoscale currents at an upper-ocean front. (September 2021) - Verma, V.; Sarkar, S.
Abstract: The three-dimensional transport pathways, the time and space scales of vertical transport, and the dispersion characteristics (single-, pair- and multi-particle statistics) of submesoscale currents at an upper-ocean front are investigated using material points (tracer particles) that advect with the local fluid velocity. Coherent vortex filaments and eddies, generated and sustained during the evolution of baroclinic instability, dominate submesoscale (0.1 - 10 km) dynamics. These coherent structures play a crucial role in the particle transport and dispersion, which we quantify here. Particles in the central frontal region organize into vertically inclined lobes with anticyclonic circulation, each associated with a coherent eddy with cyclonic rotation. Furthermore, the coherent filaments associated with heavy/light edges of the front transfer particles from the edges to the lobes by downwelling/upwelling. This flux of new particles into the central region causes the particles circulating in the lobes to adjust, which leads to slumping of the front. The particle motion in the vertical shows multiple time scales – a fast time scale with O ( 10 m ) vertical displacement within an hour and a slower near-inertial time scale, comparable to the intrinsic time scale of the growing instability. The fast O ( 1 h ) time scale is also seen in the decorrelation of vertical velocity and the tapering of the initial ballistic growth of relative particle dispersion. The overall slumping process is slower than what one might anticipate from the large magnitude of vertical velocity in the filaments since it requires a sustained correlation over time between the lateral and the vertical motion. By tracking clouds of particles, we show that their centers of mass downwell/upwell over 1 − 2 inertial time periods, after which an adjustment follows with a sub-inertial time scale. The shape change in clusters of four particles reveals filamentogenesis, i.e. deformation into thin, needle-like structures by the coherent, anisotropic motions of the submesoscale, which occurs as a rapid process that is complete within approximately an hour. Highlights: A 3D transport pathway of coherent eddies/filaments/lobes is identified. Vertical particle motions have fast O(1 h) as well as near-inertial time scales. Restratification is slower than suggested by large vertical particle velocity. Single- and pair-particle statistics reveal long time super-diffusive behavior. Four-particle clusters are strained within an hour into filaments.